1998
DOI: 10.1159/000028694
|View full text |Cite
|
Sign up to set email alerts
|

Serial Radiography in the Infant Shaken Impact Syndrome

Abstract: Certain CT and/or MRI abnormalities have been used medicolegally to time intracranial injuries from the infant shaken impact syndrome (ISIS). For example, parenchymal hypodensities on CT scans are said to arise only after 6–48 h have elapsed postinjury, and the presence of chronic or mixed subdural hematomas suggests injury that occured 1–4 weeks prior. However, these statements are based largely upon inference from data obtained in other conditions such as ischemic anoxic injury and chronic subdural hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 21 publications
4
70
1
Order By: Relevance
“…Homogeneously hyperdense SDH was present in fewer than one-third of our cases; mixed-density SDH, containing both hyperdense and hypodense components, was present in over half of the infants in the present study, in onethird of children in our prior study, 9 and in 91% of infants with AHT in a third study by Vinchon et al 31 Mixeddensity SDH in AHT has been interpreted as prima facie evidence of serial injuries, 6,25 but this concept has recently been challenged. 9,11,32,33,39 One child in our previous study developed a hypodense subdural collection de novo on a second CT scan performed 19 hours after an initial scan showed no SDH in that region. 9 In another study of 18 infant victims of motor vehicle crashes with SDH, 3 infants had mixed-density SDH on the initial CT scan.…”
Section: Serial Changes On Ctcontrasting
confidence: 43%
See 2 more Smart Citations
“…Homogeneously hyperdense SDH was present in fewer than one-third of our cases; mixed-density SDH, containing both hyperdense and hypodense components, was present in over half of the infants in the present study, in onethird of children in our prior study, 9 and in 91% of infants with AHT in a third study by Vinchon et al 31 Mixeddensity SDH in AHT has been interpreted as prima facie evidence of serial injuries, 6,25 but this concept has recently been challenged. 9,11,32,33,39 One child in our previous study developed a hypodense subdural collection de novo on a second CT scan performed 19 hours after an initial scan showed no SDH in that region. 9 In another study of 18 infant victims of motor vehicle crashes with SDH, 3 infants had mixed-density SDH on the initial CT scan.…”
Section: Serial Changes On Ctcontrasting
confidence: 43%
“…Intracranial CT abnormalities conformed to the definitions used in the previous study. 9 Subdural hematomas were defined as hemorrhagic fluid collections located under the dura along the convexity, falx, or tentorium. Although a number of studies have confirmed that these hematomas technically lie within the inner dural border zone, the term "subdural" has achieved such widespread acceptance that we refer to these collections as subdural throughout the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaken infant syndrome is the most widely used and recognized term, although shaking alone may not account for all injuries. 3 Whatever the terminology and pathogenesis, abusive head injuries among infants represent one of the most severe forms of child abuse, with 13 to 30% mortality rates 4,5,7,8 and significant neurologic impairments in at least one half of the survivors. 9 The economic costs of abusive head injuries are significant; initial inpatient hospitalization costs average $18 000 to $70 000 per child, and average ongoing medical costs can exceed $300 000 per child.…”
mentioning
confidence: 99%
“…Other terms for this condition include shaken baby syndrome or shaken infant syndrome, shaken impact syndrome, 3 infant shaken impact syndrome, 4 infant whiplash-shake injury syndrome, 5 abusive head trauma, 6 and inflicted, nonaccidental, or intentional head injury. Shaken infant syndrome is the most widely used and recognized term, although shaking alone may not account for all injuries.…”
mentioning
confidence: 99%